Atypical presentation of streptococcus salivarius meningitis - Ali, Shahnila; Hussain, Taarif (International Journal of Research in Medical Sciences, 2017)
Patient with past medical history significant for multiple co morbidities including hypertension, diabetes mellitus, paroxysmal atrial fibrillation (on Coumadin but sub-therapeutic INR on presentation), chronic systolic congestive cardiac failure/cardiomyopathy, aortic valve stenosis, mitral valve regurgitation presented with slurred speech. Due to concern for stroke, patient received initial CT scan head which was negative and admitted for further work up including MRI. Patient was also observed to be having shortness of breath and mild hypoxia in ED. Patient also had leukocytosis on complete blood count. Initial arterial blood gases results were within normal limits. CXR showed right lower lobe infiltrates suggestive of pneumonia. Infectious work up including blood cultures were also ordered. On clinical examination, no neck rigidity or any focal weakness. No facial droop either. No neurological abnormality other than slurred speech. In addition, patient was initiated on empirical coverage for possible pneumonia with consideration of aspiration event considering a sequela of stroke. Next morning, patient was able to speak clearly and stated that he did have headache few days before presentation. LP was ordered and patient found to have meningitis. Blood cultures grew Streptococcus salivarius. Patient received ceftriaxone and discharged without any complications in stable condition.